Reaction monitoring using online vs tube NMR spectroscopy: seriously different results. (6th August 2015) - Foley, David A.; Dunn, Anna L.; Zell, Mark T.
Abstract : We report findings from the qualitative evaluation of nuclear magnetic resonance (NMR) reaction monitoring techniques of how each relates to the kinetic profile of a reaction process. The study highlights key reaction rate differences observed between the various NMR reaction monitoring methods investigated: online NMR, static NMR tubes, and periodic inversion of NMR tubes. The analysis of three reaction processes reveals that rates derived from NMR analysis are highly dependent on monitoring method. These findings indicate that users must be aware of the effect of their monitoring method upon the kinetic rate data derived from NMR analysis. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A kinetic rate analysis of three reaction processes reveals that rates derived from nuclear magnetic resonance (NMR) analysis are highly dependent on monitoring method. These findings indicate that users must be aware of the effect of their monitoring method upon the kinetic rate data derived from NMR analysis.